Outcome- and sign-dependent time preferences: An incentivized intertemporal choice experiment involving effort and money - Shohei Yamamoto; Shotaro Shiba; Nobuyuki Hanaki (Osaka University, Institute of Social and Economic Research (ISER), 2024)
Previous research consistently identified differences in time preferences between effort and monetary decisions. However, the root cause of this difference- whether it stemmed from the intrinsic nature of the outcomes or the associated pleasurable or unpleasurable experiences-remained undefined. In response, we devised a novel two-stage experiment employing a 2 2 design contrasting outcomes (money and effort) and domains (pleasant and unpleasant). This approach allowed for the incentivization of all decisions, including those involving future monetary losses. Our study reveals sign-dependent preferences, showing varying degrees of impatience across pleasant or unpleasant experiences in monetary or effort-related choices. We also observed outcome-dependent preferences, particularly highlighting a higher level of impatience in unpleasant monetary choices compared with their effort-based counterparts. However, the degree of present bias did not differ across the four conditions.
Keywords: C91; D91; 330; time preferences; losses; incentivized experiment